Molecular studies on pregnancy with mouse models. Issue 13 (February 2020) - Wu, San-Pin; Emery, Olivia M; DeMayo, Francesco J
Abstract : Pregnancy is a complex process that involves crosstalk among multiple cell types in both the endometrial and myometrial compartments at the maternal side to support the fetus. Genetically engineered mouse models have served as a major platform to dissect the convolute genetic interactions in a physiological context. Combining with various applications of next generation sequencing and genome editing, functional assays by mouse models have expanded the spectrum to include both coding and noncoding genome. The present review will highlight recent findings that are primarily based on studies of mouse models with emphasis on pathways for endometrial receptivity and myometrial contraction. Emerging novel technologies that may advance the research in these two aspects will also be discussed.